Effect of saline solutions and salt stress on seed germination of sorne tropical forest tree species - Agboola, D A (Universidad de Costa Rica, 1998)
The effect of several saline solutions (as given by six salts) and salt stress (as given by 0.1 - 2 m sodium chloride solutions) on the gerrnination of seeds of six selected tropical forest Iree s pecies was investi gated. Saline solutions (O.2 m) of the six salts used had hi ghly si gnificant effects on seed gerrnination in most of the tree s pecies. Sodium sulphate ( Na 2So4) perrnitted gerrnination in the seeds of Ceibapentandra and Tectona grandis presoaked in its 0.2m solution for 36 and 48h respeetively. The Zine sulphate (ZnS04) solution enhanced the gerrnination of seeds of Terminalia ivorensis and Terrnirialia superba. Solution of Potassium permanganate favoured the gerrnination of seeds of T. grandis, T. ivorensis and T. superba. In general" inerease in molar coneentration of NaCI adversely affected the gerrnination rate of seeds. Sees of the two Terminalia species could withstand NaCl salt stress. Seeds of 1: grandis have hi gh ability to withstand salt stress com paratively.